The forbidden eaudiobook - Graham, Heather (Krewe of Hunters, 2021)
She is someone's darkest desire Playing the victim of a vampire king on an island off New Orleans is actress Avalon Morgan's creepiest role to date. It's also scary good fun—until the victim of a real killer is discovered on set, laid out for all to see. With production shut down, Avalon can't stop thinking about the chilling crime scene, or Grayson Avery, the investigator working the case. With a rising body count and zero leads, Gray can't help but be impressed by Avalon's amateur sleuthing, which takes her to the darkest corners of the internet, where killers confess their crimes. One such account is a dead ringer for the murders, but when the evidence vanishes, nobody believes Avalon—except for Gray. With no one they can trust, Avalon and Gray are determined to unbury the truth at any cost, but a return to the deadly island could be the last thing they do. Krewe of Hunters Book 1: Phantom Evil Book 2: Heart of Evil Book 3: Sacred Evil Book 4: The Evil Inside Book 5: The Unseen Book 6: The Unholy Book 7: The Unspoken Book 8: The Uninvited Book 9: The Night Is Watching Book 10: The Night Is Alive Book 11: The Night Is Forever Book 12: The Cursed Book 13: The Hexed Book 14: The Betrayed Book 15: The Silenced Book 16: The Forgotten Book 17: The Hidden Book 18: Haunted Destiny Book 19: Deadly Fate Book 20: Darkest Journey Book 21: Dying Breath Book 22: Dark Rites Book 23: Wicked Deeds Book 24: Fade to Black Book 25: Pale as Death Book 26: Echoes of Evil Book 27: The Summoning Book 28: The Seekers Book 29: The Stalking Book 30: Seeing Darkness Book 31: Deadly Touch Book 32: Dreaming Death Book 33: The Unforgiven